2013
DOI: 10.1095/biolreprod.112.106526
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Concentrations of Retinoic Acid Induce Stimulation by Retinoic Acid 8 and Promote Entry into Meiosis in Isolated Pregonadal and Gonadal Mouse Primordial Germ Cells

Abstract: In the present study, we demonstrate that minimal concentrations (≤ 1 nM) of retinoic acid (RA), equivalent to the quantity contaminating serum-containing culture medium, are sufficient to promote meiotic entry and progression through meiotic prophase I (MPI) stages in isolated 12.5-days postcoitum (dpc) XX and XY mouse primordial germ cells (PGCs) in culture. Similarly, we found that the same low RA concentration up-regulated or induced stimulation by retinoic acid 8 (Stra8) in such cells, both at mRNA and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 63 publications
5
19
0
Order By: Relevance
“…Based on these findings, the authors hypothesized that PGCs transition into meiotic germ cells (oocytes) in a gonad-independent, and therefore cell-autonomous, manner. This hypothesis was further supported by several in vitro studies [13,2123], showing, for instance, that PGCs isolated from E10.5 mouse embryos of both sexes continue to develop in vitro and initiate meiosis at approximately the same time as meiotic entry occurs in vivo [13,22,23]. …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Based on these findings, the authors hypothesized that PGCs transition into meiotic germ cells (oocytes) in a gonad-independent, and therefore cell-autonomous, manner. This hypothesis was further supported by several in vitro studies [13,2123], showing, for instance, that PGCs isolated from E10.5 mouse embryos of both sexes continue to develop in vitro and initiate meiosis at approximately the same time as meiotic entry occurs in vivo [13,22,23]. …”
Section: Introductionmentioning
confidence: 76%
“…The authors who proposed the cell-autonomous hypothesis considered E10.5 PGCs to be pre-gonadal germ cells [22,23]. However, we recently showed that the marker of genital ridge formation, GATA4, is expressed as early as E10.0 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal oocytes of mouse ovaries cultured in vitro progressing throughout the early stages of meiotic prophase I is slower than that in vivo, because in vitro culture conditions still are unable to fully meet the needs of oocyte development. Most interestingly, ActA appears to participate in the control of meiotic progression by modulating the expression of members of the RA system, namely through down-regulation of the RA degradation enzyme CYP26B1 and up-regulation of RARs [20][21][30][31]. According to the current more accepted model, female PGCs after arrival at the gonadal ridges are induced by the somatic environment, likely through RA, to activate the Stra8 gene [20,29].…”
Section: Discussionmentioning
confidence: 99%
“…According to the current more accepted model, female PGCs after arrival at the gonadal ridges are induced by the somatic environment, likely through RA, to activate the Stra8 gene [20,29]. STRA8 protein induces the mitotic-meiotic switch and drives female PGCs into meiosis [20][21][29][30]. Other unknown factors are then required for the correct progression throughout meiotic prophase I up to the diplotene stage [29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation